Fundamental managerial accounting concepts - Edmonds, Thomas P.; Edmonds, Cindy D.; Tsay, Bor-Yi; Olds, Philip R.; Schneider, Nancy W. (Boston : McGraw-Hill/Irwin, 2006)
Business
Keywords: Managerial accounting; Management accounting; Cost behavior; Cost management; Cost control; Profit; Performance evaluation